Inhibiting and other effects of hydrogen during gasification: Further insights from FT-Raman spectroscopy - Tay, H.; Kajitani, S.; Zhang, Shu; Li, Chun-Zhu (Elsevier Ltd, 2013)
Hydrogen as a gasification product gas is always present in a practical gasifier. Its inhibition of char gasification is always an important consideration in the design and operation of the gasifier. This study aims to provide further insights into the roles of hydrogen during gasification by characterising the chars at varying levels of conversion using FT-Raman spectroscopy. The char samples were prepared from the gasification of a Victorian brown coal at 800 °C in 15% H2, 15% H2O or a mixture of 15% H2 and 15% H2O (all balanced with inert gas argon) in a fluidised-bed/fixed-bed reactor. In addition to its chemisorption on the char surface to reduce the availability of active sites for char to react with other gasifying agents such as H2O in this study, hydrogen also influenced the changes in char structure, including the oxygenation/ deoxygenation of char. Despite the involvement of hydrogen in the gasification reactions, hydrogen has not caused permanent hydrogenation of char to form significant sp3-rich structures within the char.